2007
DOI: 10.1038/sj.onc.1210762
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional control of megakaryocyte development

Abstract: Megakaryocytes are highly specialized cells that arise from a bipotent megakaryocytic-erythroid progenitor (MEP). This developmental leap requires coordinated activation of megakaryocyte-specific genes, radical changes in cell cycle properties, and active prevention of erythroid differentiation. These programs result from upregulation of megakaryocyte-selective transcription factors, downregulation of erythroid-selective transcription factors and ongoing mediation of common erythro-megakaryocytic transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 62 publications
(85 reference statements)
0
51
0
Order By: Relevance
“…There is evidence that the competition between KLF1 and FLI1 on one hand 8,9,40 and the expression level of MYB 41,42 on the other hand regulate the MEP fate, and that several other transcription factors such as GATA1, GATA2, and NFE2 are necessary for both erythroid and MK differentiation. [5][6][7] Our study demonstrates that a distinct pattern of transcription factors and cytokine receptors is associated with the 3 cellular subsets that were analyzed. When the 3 global populations were considered, the progressive commitment was evidenced by a decrease in EPOR/KLF1 gene expression and an increase in AML1 and GABPA only in MK cells, whereas commitment to the erythroid lineage was associated with a decrease in MPL/FLI1/AML1/GABPA/GATA2 gene expression and an increase in EPOR/KLF1 gene expression.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There is evidence that the competition between KLF1 and FLI1 on one hand 8,9,40 and the expression level of MYB 41,42 on the other hand regulate the MEP fate, and that several other transcription factors such as GATA1, GATA2, and NFE2 are necessary for both erythroid and MK differentiation. [5][6][7] Our study demonstrates that a distinct pattern of transcription factors and cytokine receptors is associated with the 3 cellular subsets that were analyzed. When the 3 global populations were considered, the progressive commitment was evidenced by a decrease in EPOR/KLF1 gene expression and an increase in AML1 and GABPA only in MK cells, whereas commitment to the erythroid lineage was associated with a decrease in MPL/FLI1/AML1/GABPA/GATA2 gene expression and an increase in EPOR/KLF1 gene expression.…”
Section: Discussionmentioning
confidence: 98%
“…They are homodimeric class I cytokine receptors, and both require JAK2 for signaling. 3,4 Numerous transcription factors, such as GATA2, GATA1, FOG1, TAL1/SCL, GFI1B, and NFE2, are critical for both erythroid and MK development, [5][6][7] whereas others are more dedicated for unilineage differentiation, such as the erythroid EKLF (KLF1) 8,9 and MYB 10 or the MK FLI1, 11 GABPA, 12 and AML1. 13 Studies of adult hematopoiesis, both in human and mice, have shown that the erythroid and MK lineages arise from a bipotential megakaryocyte-erythroid progenitor (MEP), [14][15][16] a separate entity with no lymphoid and granulomonocytic potential.…”
Section: Introductionmentioning
confidence: 99%
“…During development, the decision to leave the self-renewing state and selection of a differentiation pathway are regulated by transcription factors (TFs) [3-6]. Intense experimental studies during the past two decades have suggested that tight regulation of HSC differentiation is controlled by the interaction of a number of genetic and epigenetic regulators of gene transcription, including the two TFs PU.1 and GATA-1.…”
Section: Introductionmentioning
confidence: 99%
“…they repress the production of each other [7-9]. In the erythrocyte/megakaryocite lineage high expression levels of gene GATA-1 and low levels of PU.1 were detected [6,10]; conversely, in the granulocyte/macrophage lineage higher expression levels of PU.1 and low levels of GATA-1 were measured [5,11]. However, the initial progenitor cells stay in the third state that has low-level activation of both genes PU.1 and GATA-1 .…”
Section: Introductionmentioning
confidence: 99%
“…9 The specific combination of transcription factors allowing erythrocytic or megakaryocytic lineages commitment remains poorly understood. 10,11 Indeed, both lineages are dependent on many common transcription factors including Gata1, Tal1, Nfe2, Gfi1b, Zbp89, as well as cofactors like Fog1, Lmo2, or Ldb1 acting in large multiprotein complexes such as Fog1/Gata1/Zbp89 12 or Gata1/Tal1/Lmo2/Ldb1. 13 No differential requirement of these factors for either lineage has been reported to date.…”
Section: Introductionmentioning
confidence: 99%